Perlindungan Hukum Pekerja Harian Lepas di PT. Madina Agro Lestari Perspektif Undang-Undang dan Fiqih Siyasah - Hutabarat, Yurliani; Hsb, Putra Halomoan (Jurnal El-Thawalib, 2023)
The problem in this research is the legal protection for casual daily workers at PT. Madina Agro Lestari in Attitude Village, Muara Batang Gadis District, Mandailing Natal Regency. Because there are still many casual daily workers who do not get some rights.  Legal protection for casual daily workers is a work contract, work safety and welfare. The purpose of this study is to describe and analyze the legal protection for casual daily workers at PT. Madina Agro Lestari. The formulation of the research problem is how the legal protection for casual daily workers at PT. Madina Agro Lestari, what is the review of Fiqh siyasah regarding legal protection for casual daily workers at PT. Madina Agro Lestari, and what are the inhibiting and supporting factors for legal protection against casual daily workers at PT. Madina Agro Lestari. The method in this research is empirical normative with a sociological juridical approach, namely describing the conditions in the field as they are and the labor law which is the benchmark in this research. The data collection instrument used consisted of observation , interview , and documentation. The result of this research is legal protection for casual daily workers at PT. Madina Agro Lestari work agreements, worker wages, occupational safety and health, fiqh siyasa, view that humans are all the same and Islam is hostile to people who do not give the rights of others.  The obstacles faced are that there are still many casual daily workers who have not received perfect legal protection due to the low education of casual daily workers, and from companies.